In the beginning: Role of autonomy support on the motivation, mental health and intentions of participants entering an exercise referral scheme - Rouse, P.; Ntoumanis, Nikos; Duda, J.; Jolly, K.; Williams, G. (2011)
Self-determination theory (Deci & Ryan, 2000, Intrinsic motivation and self-determination in human behaviour. New York: Plenum Publishing) highlights the impact autonomy supportive environments can have on exercise motivation and positive health outcomes. Yet little is known about whether differential effects occur as a function of which significant other is providing this support. Further, no research has examined the relationship between motivation and the social environment with participants' mental health and intentions to be physically active before entering an exercise intervention. Study participants were 347 British adults who were about to start an exercise referral scheme. Regression analyses revealed that the effects of autonomy support on mental health and physical activity intentions differed as a function of who provided the support (offspring, partner or physician), with the offspring having the weakest effects. A structural model was supported, indicating that autonomy support and more autonomous regulations led to more positive mental health outcomes and stronger intentions to be physically active. Knowledge of the social environmental and personal motivation of those about to commence an exercise programme can provide important insights for professionals supporting such efforts. © 2011 Taylor & Francis.